HPV E6 Proteins Target Ubc9, the SUMO Conjugating Enzyme - Heaton, Phillip R. (2011)
The human papillomavirus oncogenic protein, E6, interacts with a number of cellular proteins, and for some targets, E6 directs their degradation through the ubiquitin-proteasome pathway. Post-translational modification with ubiquitin-like modifiers, such as SUMO, also influences protein activities, protein-protein interactions, and protein stability. We report that the high risk HPVE6 proteins reduce the intracellular quantity of the sole SUMO conjugation enzyme, Ubc9, concomitant with decreased host sumoylation. E6 did not significantly influence transcription of Ubc9, indicating that the effects were likely at the protein level. Consistent with typical E6-mediated proteasomal degradation, E6 bound to Ubc9 in vitro, and required E6AP for reduction of Ubc9 levels. Under stable E6 expression conditions in differentiating keratinocytes there was a decrease in Ubc9 and a loss of numerous sumoylated targets indicating a significant perturbation of the normal sumoylation profile. While E6 is known to inhibit PIASy, a SUMO ligase, our results suggest that HPV E6 also targets the Ubc9 protein to modulate host cell sumoylation, suggesting that the sumoylation system may be an important target during viral reproduction and possibly the subsequent development of cervical cancer.